Research on boundary slip of hydrostatic lead screw under different driving modes - Yandong Liu (Nature Portfolio, 2021)
Abstract The flow state of oil film in the hydrostatic lead screw directly affects the transmission performance of the screw pair. The static and dynamic characteristics of a new type of double driven hydrostatic screw-nut pair (DDHSNP) are studied under different motion modes. The boundary condition of navier slip model is introduced into the lubricating mathematical model of DDHSNP, and the influences of boundary slip on the axial bearing capacity, axial stiffness and damping coefficient in micro scale are researched by finite difference method. The results show that when the motor runs at high speed (the rotating speed range of the screw and nut driven motor is 1000–9000 rpm), the existence of boundary slip leads to a improvement of the axial bearing capacity and stiffness coefficient of DDHSNP in the case of single-drive operation and dual-drive differential feed (the range of rotation difference is 10–100 rpm), which is more obvious under the single-drive mode. The increase rate of stiffness coefficient induced by boundary slip is much larger than that of bearing capacity. In addition, the boundary slip has little effect on the damping coefficient of DDHSNP in either single drive operation or dual drive differential operation.